2016
DOI: 10.1177/1359104516658190
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing disruptive mood dysregulation disorder: Integrating semi-structured and unstructured interviews

Abstract: The newest iteration of the Diagnostic and Statistical Manual-fifth edition (DSM-5), is the first to include the diagnosis of disruptive mood dysregulation disorder (DMDD). The assessment and diagnosis of psychopathology in children are complicated, particularly for mood disorders. Practice can be guided by the use of well-validated instruments. However, as this is a new diagnosis existing instruments have not yet been evaluated for the diagnosis of DMDD. This study seeks to provide a method for using existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Open-ended semi-structured questions (McIntosh and Morse, 2015; Cachia and Millward, 2011), unstructured interviews (McTate and Leffler, 2017; Chauhan, 2019) and informal as well as direct participatory observations (Clow and Makriyannis, 2011) were used during interactions with key stakeholders. This approach allowed for follow-up questions that enhanced the clarity of thoughts and emergence of themes in the interviewee's context.…”
Section: Methodsmentioning
confidence: 99%
“…Open-ended semi-structured questions (McIntosh and Morse, 2015; Cachia and Millward, 2011), unstructured interviews (McTate and Leffler, 2017; Chauhan, 2019) and informal as well as direct participatory observations (Clow and Makriyannis, 2011) were used during interactions with key stakeholders. This approach allowed for follow-up questions that enhanced the clarity of thoughts and emergence of themes in the interviewee's context.…”
Section: Methodsmentioning
confidence: 99%
“…The final technique of the study was semi-structured individual interviews which were conducted to acquire a sufficient comprehension of the topic, and to enable additional questioning based on a participant's response (McTate and Leffler, 2017). Semi-structured individual interviews seek to provide a deeper comprehension and exploration of the complex problems, structures, operations and policies that pervade participants' stories (Ahorbo, 2014; Manly, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…4 McTate and Leffler's review of existing structured interview instruments has suggested the Children's Interview for Psychiatric Syndromes, while diagnostically narrow, as a useful screening tool for DMDD. 25 The Mini-International Neuropsychiatric Interview for Children and Adolescents is considered weak due to a lack of items specific for DMDD symptoms. 25 Other tools such as Development and Wellbeing Assessment or Clinical Global Impression scale are much broader and are used as part of psychiatric evaluation.…”
Section: Diagnostic Dilemmamentioning
confidence: 99%
“…25 The Mini-International Neuropsychiatric Interview for Children and Adolescents is considered weak due to a lack of items specific for DMDD symptoms. 25 Other tools such as Development and Wellbeing Assessment or Clinical Global Impression scale are much broader and are used as part of psychiatric evaluation. These scales are not diagnostic for irritability in DMDD because the symptom is considered a nonspecific indicator and is related to several other psychiatric disorders.…”
Section: Diagnostic Dilemmamentioning
confidence: 99%